2017
DOI: 10.22260/isarc2017/0120
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Concrete Compressive Strength from Early Age Test Result Using an Advanced Metaheuristic-Based Machine Learning Technique

Abstract: -Determining accurate concrete strength is a major civil engineering problem. Test results of 28-day concrete cylinder represent the characteristic strength of the concrete that has been prepared and cast to form the concrete work. It is important to wait 28 days to ensure the quality control of the process, although it is very time consuming. Machine learning techniques are progressively used to simulate the characteristic of concrete materials and have developed into an important research area. This study pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…LS-SVM was first developed by [8] as an improved version of the support vector machine (SVM). As a data mining technique, LS-SVM has been successfully applied in many civil engineering-related problems [14][15][16][17]. LS-SVM utilizes a cost function based on the least squares principle as opposed to the quadratic loss function that had been used in the original SVM [18].…”
Section: Regression Model: Ls-svmmentioning
confidence: 99%
“…LS-SVM was first developed by [8] as an improved version of the support vector machine (SVM). As a data mining technique, LS-SVM has been successfully applied in many civil engineering-related problems [14][15][16][17]. LS-SVM utilizes a cost function based on the least squares principle as opposed to the quadratic loss function that had been used in the original SVM [18].…”
Section: Regression Model: Ls-svmmentioning
confidence: 99%
“…Research has shown that there is an increase in prediction accuracy when metaheuristic algorithm is used as the optimizer for model selection and has improved prediction performance in various engineering problems [2,6,9,10]. Many studies have shown that the SOS algorithm is better when compared to other metaheuristic algorithms in finding the optimal solutions to problems involving complex and nonlinear optimization [2,11].…”
Section: Model Selection In the Training Phasementioning
confidence: 99%
“…As we have argued, diverse efforts concerning the accuracy improvement of conventional approaches illustrate the importance of this task in civil engineering. On the other hand, benefiting from optimization strategies (e.g., grey wolf optimizer [46], symbiotic organism searches [47], teaching learning-based optimization [48], etc.) has been regarded an effective idea for this purpose.…”
Section: Introductionmentioning
confidence: 99%